(X+8)=(2x-3)

Simple and best practice solution for (X+8)=(2x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (X+8)=(2x-3) equation:


Simplifying
(X + 8) = (2x + -3)

Reorder the terms:
(8 + X) = (2x + -3)

Remove parenthesis around (8 + X)
8 + X = (2x + -3)

Reorder the terms:
8 + X = (-3 + 2x)

Remove parenthesis around (-3 + 2x)
8 + X = -3 + 2x

Solving
8 + X = -3 + 2x

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-8' to each side of the equation.
8 + -8 + X = -3 + -8 + 2x

Combine like terms: 8 + -8 = 0
0 + X = -3 + -8 + 2x
X = -3 + -8 + 2x

Combine like terms: -3 + -8 = -11
X = -11 + 2x

Simplifying
X = -11 + 2x

See similar equations:

| 8-3x=5x^6 | | 2/3n-5n | | -42+15= | | X^4-6x^2+8= | | 6=4(h+3)-2 | | c=10x+1200 | | 22.6=6x-2 | | .5-.02x=.1 | | k=-3+8+(-9) | | X^5-6x^3+8x= | | 5y=10+10x | | 9log(x-3)+5=18 | | -4+(-5)+6=m | | 6e^3x=84 | | .4(x-5)=.2(10-12x)+x | | 20z(2/z-1/5z) | | 3y=10+10x | | 7x-13=190 | | 9v=24+6v | | 6+5(-4)=t | | S=48+(-2s) | | 6y+2(y-2)=5(y+1)-2 | | (x*x)+(4x)-32=0 | | 3(8bx+y)=23bx-4y | | 25a=81*100 | | -2+x+10=4x+23 | | f=-52+52 | | 25a=9*100 | | 9t-7=-7+4t | | g-7=12 | | 13x/3=1521 | | 33+y=4 |

Equations solver categories